Nuevos datos acerca del área suburbana de Caura - Buzón Alarcón, Manuel (ROMULA, 2012)
Durante la Intervención Arqueológica Preventiva realizada en el nº 16 de la calle Cervantes de Coria del Río, documentamos parte de un complejo alfarero situado cronológicamente en el siglo I de nuestra era, que quedará soterrado a principios del siglo III por diferentes niveles de habitación. Posteriormente durante el siglo IV, el espacio es ocupado por una necrópolis. --------------------------------------------------------------------- We present the combined results of the urgent excavation and construction survey taken place at the lot 16 on Cervantes street. The stratigraphic sequence covers the different periods of use and occupation of this city lot, beginning at Roman times and continuing until today without interruption. The earliest evidence consists in a potter complet of 1 st century AD. This area is occupied in the 3 nd century with domestic buildings. In the 4 th century the lot covered its use as a necrópolis.